2017
DOI: 10.1038/srep45674
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Associated with Caste Determination and Differentiation in a Primitively Eusocial Insect

Abstract: In eusocial Hymenoptera (ants, bees and wasps), queen and worker adult castes typically arise via environmental influences. A fundamental challenge is to understand how a single genome can thereby produce alternative phenotypes. A powerful approach is to compare the molecular basis of caste determination and differentiation along the evolutionary trajectory between primitively and advanced eusocial species, which have, respectively, relatively undifferentiated and strongly differentiated adult castes. In the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 60 publications
1
30
0
1
Order By: Relevance
“…Histone modifications have been shown to be involved with plasticity, for example changes in histone acetylation alter the behavior of major workers of the ant species Camponotus floridanus, making them more similar to the behavior of minor workers (Simola et al 2016). Variation in microRNA expression levels has been identified in both honeybee (Ashby et al 2016) and bumblebee (Collins et al 2017) castes. However, the most active research in this area has been focused on DNA methylation (Glastad et al 2015).…”
Section: Impact Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Histone modifications have been shown to be involved with plasticity, for example changes in histone acetylation alter the behavior of major workers of the ant species Camponotus floridanus, making them more similar to the behavior of minor workers (Simola et al 2016). Variation in microRNA expression levels has been identified in both honeybee (Ashby et al 2016) and bumblebee (Collins et al 2017) castes. However, the most active research in this area has been focused on DNA methylation (Glastad et al 2015).…”
Section: Impact Summarymentioning
confidence: 99%
“…) and bumblebee (Collins et al. ) castes. However, the most active research in this area has been focused on DNA methylation (Glastad et al.…”
mentioning
confidence: 99%
“…Histone modifications have been shown to be involved with plasticity, for example changes in histone acetylation alter the behaviour of major workers of the ant species Camponotus floridanus , making them more similar to the behaviour of minor workers (Simola et al , 2016). Variation in microRNA expression levels has been identified in both honeybee (Ashby et al , 2016) and bumblebee (Collins et al , 2017) castes. However the most active research in this area has been focused on DNA methylation (Glastad et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Functional genomic techniques, such as RNA‐Seq, provide an unbiased view into genome‐wide transcriptional changes and have been applied to microparasite–insect systems to elucidate genes underlying complex altered host phenotypes (Choi et al ., ; Geffre et al ., ). For the bumblebee, recent developments in genomics and transcriptomics have provided the tools to explore important aspects of host biology, including phenotypic polymorphism (Colgan et al ., ; Harrison et al ., ), caste differentiation (Collins et al ., ; Woodard et al ., ), mating success (Manfredini et al ., ) and diapause regulation (Amsalem et al ., ). In relation to pathogen response, previous transcriptomic studies have identified changes in host immune expression in response to the trypanosomatid Crithidia bombi (Barribeau et al ., ) and bacterial challenge (Barribeau et al ., ).…”
Section: Introductionmentioning
confidence: 99%